Quels modèles d’accompagnement pour les stagiaires en enseignement afin de favoriser l’articulation théorie-pratique ? - Gouin, Josee-Anne; Hamel, Christine (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
This article presents the challenges faced by trainers in relation to supporting their trainees in the development of theory-to-practice links in the course. The objective of the research is to describe the perceptions of trainees in secondary education in relation to the practices of each of their trainers, associate teacher, university supervisor and didactic teacher, during the planning, class management and analysis of the development of a training course in an internship III. Supported by a conceptual framework making it possible to study the coaching practices of trainers, a questionnaire was developed and distributed to third-year trainees of the baccalaureate in secondary education after five weeks of internship in a school environment. The analysis of the results raises questions about the support model to promote practical theory links in the training of future teachers in Quebec.